Ibero-American Network as a Collaborative Strategy to Provide Tools for the Development of Phytopharmaceuticals and Nutraceuticals - Buera, María del Pilar; Abirached, Cecilia; Alamilla-Beltrán, Liliana; Busch, Verónica María; Santos, Cristina Isabel dos; Farroni, Abel Eduardo; Favre, Leonardo Cristian; Fernández-Varela, Aldo; Freire-Costa, Fabiano; Gabilondo, Julieta; Galante, Micaela; Hidalgo, María Eugenia; et al. (Wiley, 2021)
The increasing trend for using natural ingredients for nutraceuticals and phytopharmaceuticals development triggers the study of non-traditional sources for phytopharmaceuticals development, such as underexploited plants and agroindustrial wastes. The extraction, characterization and stabilization of bioactive compounds are intricate due to their low concentrations and their complex interactions in the vegetable matrix. New simple, ecological and efficient technologies are being developed to overcome the disadvantages of traditional extraction procedures, and many strategies should be developed to preserve their bioactivity. Oxidative reactions and protein glycation are two of the main deteriorative reactions affecting biological molecules and functionality loss in vitro and in vivo. Thus, efforts have been extended in search of edible plants with antioxidant or antiglycant properties. This chapter is an outcome of the CYTED Iberoamerican network 415RT0495, which task was to promote the valorization of subvaluated sources of bioactive compounds for food and medical uses.